Takhrij and Syarah Hadith of Chemistry: Prohibition of Drinking Khamer in a Chemical Perspective - Herna Novi Kurnianti; Elzha Gita Lestari; Wahyudin Darmalaksana; Ahmad Soheh Mukarom; Tina Dewi Rosahdi (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet sallallaahu 'alaihi wassalam related to khamer. The research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The results and discussion of this study is that khamer as a prohibited drink contains ethanol and methanol which can be addictive for the consumer. The effect of alcohol consumption on different individuals, there are those who experience excessive excitement to make themselves more active because the alcohol concentration increases in the blood. The conclusion of this study is that the hadith has authentic quality which is strengthened by its proof through chemical analysis, that this khamer is a drink that can be addictive and dangerous for the consumer.